Digital Transformation and MSME Financial Performance: Systematic Literature Review and Bibliometric Analysis - Fazlur Rahman Rahawarin; Eko Soetjipto, Budi; Wardoyo, Cipto (Economics and Business Journal (ECBIS), 2023)
Digital transformation is a hot topic for research. Various technological developments encourage various organizations to carry out digital transformation to achieve organizational goals. This is experienced by SMEs in running their business. Various studies that have been conducted have yielded inconsistent results regarding the adoption of digital transformation for MSMEs. This article discusses the extent to which previous research has explored digital transformation carried out by MSMEs that can have an impact on financial performance. This article uses a systematic literature review and bibliometric analysis to explore previous research related to the digital transformation of MSMEs